BIOEFFICACY OF ALLIUM SATIVUM EXTRACT IN THE CONTROL OF TRICHODINA AND EPISTYLIS SPP OF CLARIAS GARIEPINUS IN GWAGWALADA TOWN FCT, ABUJA - U.N., GIMBA, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Parasitological examination was carried out in one hundred and forty-five naturally collected Clarias gariepinus from Usuma River in Gwagwalada. It revealed skin and gill infestation with ectoparasitic protozoan Trichodina and Epistylis and monogenean Tetrahymena spp. with average 20, 15 and 25%, respectively. The average total ectoparasitic infestation in the examined catfish was 60%.The significance of herbal control measures using A. sativum as a new method to eradicate such parasites, was evaluated. A bioassay of 96 hours LC50 of A. sativum emphasized that its value was 192mg/L. The herbal control with A. sativum was safe and effective to treat the ectoparasitic protozoa Trichodina and Epistylis spp. at dose 20mg/L, but not suitable for treating the monogenean Tetrahymena spp.